State behavior and crystal growth kinetics of sucrose and corn syrup mixtures. (September 2015) - Chen, Jiahui; Nowakowski, Christine; Green, Dan; Hartel, Richard W.
Highlights: The impact of sucrose to corn syrup ratio was more evident on solubility temperature than T g . Corn syrup reduced the magnitude of crystal growth rates; higher level having greater effects. The addition of corn syrup diminished the regions of high crystal growth rates. The extent of the GRD changed proportionally with growth rate. Abstract: Effects of 63DE (dextrose equivalent) commercial corn syrup on the state behavior and crystal growth rate of sucrose and corn syrup mixtures in thin films (1.08 mm) were investigated using DSC and polarized light microscopy. Glass transition temperature ( T g ) and solubility temperature increased significantly as moisture content decreased from 16.75% to 3.75%. Additionally, higher levels of corn syrup depressed solubility temperature but at the levels studied, showed no apparent effect on T g . Addition of corn syrup significantly decreased sucrose crystal growth rate. For systems containing 14% and 30% corn syrup, growth rates measured between 40 and 120 °C ranged from 5.6 to 3400 μm 2 /min and 1.8 to 470 μm 2 /min, respectively. Growth rate dispersion (GRD) was observed for all conditions and the extent of the GRD increased with increasing growth rate. By overlaying crystallization rate zones on the state diagram, the competing effects of supersaturation driving force and molecular mobility inhibition on sucrose crystal growth rates were clearly observed.